Numerical analysis of a caprock integrity during oil production by steam-assisted gravity drainage method - Anastasiia Kostina; Maxim Zhelnin; Oleg Plekhov (Fracture and Structural Integrity)
The work is devoted to the investigation of a caprock integrity during oil production by steam-assisted gravity drainage method. An originally proposed thermo-hydro-mechanical model was used for the evaluation of mechanical loading acting on the over-burden. The model includes mass conservation laws, the energy conservation law and the linear momentum balance. Filtration of each phase of the three-phase flow (steam, oil and water) is described by Darcy’s law. Inelastic deformations are described by the phenomenological viscoplastic model based on Drucker-Prager yield criterion.  The effect of  the porosity evolution induced by the propagation of the steam chamber within the reservoir on the oil production rate and the caprock integrity is studied. It has been shown that the oil production rate is strongly depend on the prevailing physical mechanism of the porosity evolution.  Reservoirs characterized by the volumetric strain mechanism of the porosity evolution produce slightly higher values of the mechanical loadings acting on the over-burden.